Efektivitas pelaksanaan supervisi manajerial dalam upaya meningkatkan kinerja organisasi pendidikan - Agung D., Prasetyo; Heryana, Nella; Putri A., Viska; Putri W., Tiyas; Aurelia, Azzahra; Hayat, Ainul; Khumaidi, Nukman (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2022)
Supervision is an activity that needs to be done to see and evaluate the performance of educational institutions. Managerial supervision in its implementation is still not significant in improving the performance of educational organizations because there are several obstacles. Therefore, researchers are interested in researching the implementation of managerial supervision in educational units and the effect of managerial supervision as a tool to improve the performance of educational organizations so that later learning activities can run as expected. In writing this article, the literature review method was used through various sources to obtain data and information. The sources studied in the preparation of this scientific article are books, journals, and articles on several online websites. The purpose of this article is to carry out case studies and provide educational supervisors with an understanding of managerial supervision. In conclusion, the implementation of managerial supervision in schools has an important influence, especially in terms of improving the performance of educational organizations and there are several ways that can be done to increase the effectiveness of the implementation of managerial supervision in schools.